First detection of a novel ‘unknown host’ flavivirus in a Malaysian rodent - Blasdell, Kim R.; Wynne, James W.; Perera, David; Firth, Cadhla (Microbiology Society, 2021)
Current phylogenetic analysis of the flavivirus genus has identified a group of mosquito-borne viruses for which the vertebrate hosts are currently unknown. Here we report the identification of a novel member of this group from a peridomestic rodent species (Sundamys muelleri) collected in Sarawak, Malaysia in 2016. We propose to name this novel flavivirus Batu Kawa virus after the location in which it was identified, with the abbreviation BKWV. Characterization of the BKWV genome allowed identification of putative mature peptides, potential enzyme motifs and conserved structural elements. Phylogenetic analysis found BKWV to be most closely related to Nhumirim virus (from Brazil) and Barkedji virus (from Senegal and Israel). Both of these viruses have been identified in Culex mosquitoes and belong to a group of viruses with unknown vertebrate hosts. This is the first known report of a member of this group of viruses from a potential mammalian host.